2017
DOI: 10.1002/jlb.2ma0817-312r
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced phosphorylation of sphingosine and ceramide sustains the exuberant proliferation of endothelial progenitors in Kaposi sarcoma

Abstract: Endothelial colony-forming cells (ECFCs), a unique endothelial stem cell population, are highly increased in the blood of Kaposi sarcoma (KS) patients. KS-derived ECFCs (KS-ECFCs) are also endowed with increased proliferative and vasculogenic potential, thus suggesting that they may be precursors of KS spindle cells. However, the mechanisms underlying the increased proliferative activity of KS-ECFCs remain poorly understood. Sphingosine-1-phosphate (S1P) and ceramide-1-phosphate (C1P) are metabolically interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…Moreover, the anti-apoptotic pathway induced by C8-C1P involved the up-regulation of BCL-2 and ERK 1/2 signaling. These results are in concordance with previous reports showing that natural C16-C1P is able to upregulate another BCL-2 subfamily member -BCL-XLin apoptotic macrophages (30), and that the phospho-sphingolipid C1P triggers ERK and AKT signaling pathways in several cell types (9,29,31,32). Additionally, Jung et al showed that C2, C6, and C8 ceramides as well as C8 ceramide-1-phosphate inhibited iNOS and proinflammatory cytokines in LPS-stimulated BV2 microglial cells and rat primary microglia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the anti-apoptotic pathway induced by C8-C1P involved the up-regulation of BCL-2 and ERK 1/2 signaling. These results are in concordance with previous reports showing that natural C16-C1P is able to upregulate another BCL-2 subfamily member -BCL-XLin apoptotic macrophages (30), and that the phospho-sphingolipid C1P triggers ERK and AKT signaling pathways in several cell types (9,29,31,32). Additionally, Jung et al showed that C2, C6, and C8 ceramides as well as C8 ceramide-1-phosphate inhibited iNOS and proinflammatory cytokines in LPS-stimulated BV2 microglial cells and rat primary microglia.…”
Section: Discussionsupporting
confidence: 93%
“…A well-reported property of C1P is its ability to induce cell survival, counteract apoptotic stressors, and induce proliferation in different models (8,28,29). Here we showed that both types of phospholipids, the natural C16-C1P and the synthetic C8-C1P, promote antiapoptotic activity after serum deprivation in freshly isolated human CD14 + monocytes.…”
Section: Discussionmentioning
confidence: 54%
“…Interestingly, endothelial colony-forming cells, a unique endothelial stem cell population, are highly increased in the blood of Kaposi sarcoma patients and have the ability to efficiently produce high levels of C1P (and S1P), a fact that significantly contributes to their increased proliferative properties. Additionally, exogenous C1P and S1P were found to stimulate proliferation of these cells [ 84 ], suggesting that both bioactive sphingolipids are relevant for development of Kaposi sarcoma; targeting C1P and S1P signaling may turn out to be a useful therapeutic approach to treat the disease.…”
Section: Implication Of Cerk/c1p In Lung Cancermentioning
confidence: 99%
“…C1P-enhanced pancreatic tumor cell migration and invasion are dependent upon PI3K, Akt1, mTOR1, ERK1-2, and RhoA/ROCK signaling pathways [39]. CerK activity is required in the proliferation of neuroblastoma cells [40], of breast cancer cells [41], and of Kaposi sarcoma stem cells [42]. In metastatic breast cancer cells, CerK is upregulated and contributes to the migration and invasion through PI3K/Akt/Rho kinase activation [43].…”
Section: Ceramide-1-phosphatementioning
confidence: 99%